Gorgias / Translated with an introduction by;Walter Hamilton. - Plato ("Middlesex, Eng.", 1983)
To judge by its bitter tone Plato's Gorgias was written shortly after the death of Socrates. Though Gorgias was a Sicilian teacher of oratory, the dialogue is more concerned with ethics than with the art of public speaking. The ability, professed particularly by the Sophists, to make the worse cause appear the better, struck Plato as the source of all corruption.
Keywords: "Plato, Gorgias"